Tourism, transport and travel management
"This book is a cohesive and comprehensive look at this multi-million dollar industry sector from a variety of perspectives relevant to the teaching of tourism. Covering all aspects of management of travel and tourism industry, this book looks at the core disciplines and the application of theory to practice." --